Traumatic History and its Psychological and Moral Consequences - Skoneczna, Magdalena (Hybris, 2025)
The article addresses the issue of traumatic historical events, collective methods of commemorating them, and their long-term psychological and moral consequences. It takes as its starting point Michał Bilewicz’s book Traumaland, which explores the impact of historical violence – war, persecution, genocide – on collective identity and cognitive attitudes. The article juxtaposes psychological diagnoses with selected philosophical categories drawn from Friedrich Nietzsche, particularly his typology of history and the concept of ressentiment. On this basis, it introduces the notion of “traumatic history” as a cultural form of commemorating collective injury, which may both sustain memory and identity and perpetuate reactive attitudes leading to ressentiment. It identifies the link between historical trauma and a morality shaped by fear, rancor and impotence, while also exploring the possibility of critically working them through. As an alternative to ressentimental fixation, the article proposes critical reflection on collective historical experience as a path toward self-knowledge and the transformation of collective identity.